원전운전지표를 이용한 원전의 안전성 변화 분석 - 박우영; Wooyoung Park (자원·환경경제연구, 2017)
본 연구는 국제원자력기구(International Atomic Energy Agency: IAEA)의 원자로정보시스템(Power Reactor Information System: PRIS)에서 제공하는 원자로 운전실적지표를 이용하여 원전의 안전성에 미치는 기술적·비기술적 요인의 역할을 분석한다. 이를 위해 안전성의 척도로 원전의 고장정지에 따른 발전손실률 (FLR: forced loss rate)을 사용했다. 1970년부터 2015년까지 전 세계에서 운영된 모든 원전으로 구성된 패널자료를 통해 분석한 결과, 기존 연구와 마찬가지로 원전의 전반적인 기술수준과 정비기술수준이 향상될수록 FLR이 하락하는 사실을 확인했다. 하지만 1986년 체르노빌 원전 사고 이후 기술적 요인이 통제된 FLR은 유의적으로 상승했다. 이는 원자력발전사업자가 체르노빌 사고 이후 원자력안전을 위해 보다 많은 기회비용을 지불하고 있다고 해석된다. Nuclear safety measures such as safety technology, culture, and regulation affects nuclear performances. This paper analyzes the change of nuclear performance by considering nuclear safety measures. Nuclear performance and technical data ranging 1970 to 2015 are collected from the Power Reactor Information System (PRIS) of IAEA. The result of panel regression analysis shows that overall engineering level, maintenance engineering and productivity decrease the forced loss rate (FLR). FLR structurally increase after Chernobyl accident in 1986 whereas after TMI and Fukushima accidents FLR didn`t show any significant changes. The structural increase of FLR after Chernobyl are likely to result from the efforts of international communities for nuclear safety culture which makes nuclear operating company pay more opportunity cost to achieve nuclear safety.